The art of the App Store : the business of Apple development - McCann, Tyson (John Wiley & Sons, 2012)
A unique behind-the-scenes look at what makes an application succeed in the App Store With this invaluable book, Tyson McCann offers a non-technical look at all aspects of the iPhone application development landscape and gets to the core of what makes a popular--and profitable--application. From knowing your customer to launching a successful app, and everything in between, this must-have guide navigates such topics as developing a concept, analyzing the competition, considerations before the launch, marketing, building a community, and maintaining market share ... to name a few. Coverage includes: Setting Your Goals, Costs, and Expectations Researching the App Store Market Knowing Your Customer Plotting the Stages of Development Guidelines and Expectations for Developing Your App Creating Free and Freemium Apps Creating Paid and Premium Apps Adopting Apple's Approach Riding the Social Networking Wave Feedback, Maintaining, and Scaling Open the vault to App Store success with this indispensable guide!